Salivary Exosomal MicroRNAs as Non-Invasive Biomarkers for Early Detection of Oral Squamous Cell Carcinoma: A Prospective Diagnostic Study - Ahmad Al Muzeal, Manal Mohammed (International Journal of Innovative Research in Medical Science, 2025)
Oral squamous cell carcinoma (OSCC) remains a major public health concern due to its late diagnosis and poor survival outcomes. Non-invasive biomarkers capable of detecting early-stage OSCC are urgently needed. Salivary exosomal microRNAs (miRNAs) have emerged as promising molecular indicators owing to their stability, specificity, and ease of collection. To evaluate the diagnostic performance of salivary exosomal miR-21, miR-31, miR-155, and miR-200c as biomarkers for early OSCC detection. This prospective case-control study included 140 participants categorized into three groups: OSCC patients (n = 60), individuals with benign oral lesions (n = 40), and healthy controls (n = 40). Saliva samples were collected, and exosomes were isolated and validated using NTA, TEM, and Western blot. Exosomal miRNAs were extracted and quantified via qRT-PCR. Statistical analyses included ANOVA, ROC curve analysis, and multivariate logistic regression. All four miRNAs were significantly elevated in OSCC patients (p < 0.001). miR-21 showed the highest diagnostic accuracy (AUC = 0.89), while the combined panel achieved an AUC of 0.93, with sensitivity and specificity exceeding 90% and 88%, respectively. Strong correlations between miRNA levels and tumor stage were observed for miR-21 and miR-155. Salivary exosomal miRNAs exhibit high diagnostic accuracy for OSCC, even in early-stage disease. This non-invasive molecular approach offers a feasible and scalable alternative to traditional diagnostic modalities and holds significant potential for integration into routine screening and surveillance protocols.